Prevalence of neurological diseases associated with cervical pain and/or signs of cervical myelopathy in French bulldogs: a retrospective analysis of 105 cases - Capasso, Michele; Canal, Sara; Balducci, Federica (Frontiers in Veterinary Science, 2024)
French bulldogs can be affected by several neurological diseases, with myelopathies representing the most frequent cause of neurological signs. Studies focusing on the epidemiology of cervical diseases in this breed are lacking. This study aims to describe the prevalence of neurological pathologies responsible for cervical pain and/or signs of cervical myelopathy, assuming that intervertebral disc herniation represents the most common disease; a second aim was to evaluate how often different pathologies coexist in this spinal region in French bulldogs.A retrospective analysis of medical records from the database of a single referral center (AniCura I Portoni Rossi Veterinary Hospital -Zola Predosa, Bologna, Italy) was performed, including French bulldogs presented for neck pain and/or neurological deficits consistent with cervical myelopathy. Clinical and imaging data were reviewed and used as inclusion criteria. Based on the number of MRI-diagnosed diseases, the eligible dogs were divided into three groups.Results: One hundred five French bulldogs met the inclusion criteria. The most commonly diagnosed condition was an intervertebral disc herniation (66.9%), followed by C2 idiopathic hypertrophic ganglioneuritis (15.1%), cervical syringomyelia (11.5%), congenital osseous malformations (1.4%), spinal arachnoid diverticula (1.4%), neoplasms (1.4%), steroid-responsive meningitis-arteritis (0.7%), traumatic vertebral fractures (0.7%), and other (0.7%). For the vast majority of dogs (75/105) a single pathology was diagnosed, with intervertebral disc herniations accounting for 86.7% of cases, involving C3-C4 IVD most commonly. In the remaining 30 dogs, two or three different and concurrent diseases were detected. Among these 30 dogs, intervertebral disc herniations still remained the most diagnosed condition, in combination with C2 idiopathic hypertrophic ganglioneuritis and syringomyelia in 19 and seven cases, respectively.The results of this study highlight that different pathologies can affect the cervical spinal cord in French bulldogs, with intervertebral disc herniations representing the most frequent condition, as previously described in the veterinary literature. In almost a third of cases, different pathologies can coexist at the cervical level. However, for cases in which different pathologies are present at the same time, it is not always possible to clearly establish their clinical significance.